Kajian Teologis Tentang Sejarah Misi Rasul Petrus - Pasra (STT Pelita Dunia, 2023)
Abstract: This research examines the historical, theological, and missionary context of the life of the Apostle Peter, highlighting the key role he played in spreading Christian teachings. Through a theological approach, this research tries to answer fundamental questions about how the mission of the Apostle Peter influenced the early development of the church and how his personal experiences interacted with the divine call. The method the author uses is literature study. This study also explores the impact of the Apostle Peter's mission on Christian theological understanding and how his contribution formed the foundation of faith in the Christian tradition. By understanding important events in the history of the Apostle Peter's mission, this research aims to provide a deeper understanding of his theological role in the mission context and present a comprehensive view regarding his influence on the development of Christian teachings. The theological implications of the Apostle Peter's mission are also detailed, highlighting its relevance in the context of contemporary Christianity. Abstrak: Penelitian ini membahas konteks historis, teologis, dan misionaris dari kehidupan Rasul Petrus, menyoroti peran kunci yang dimainkannya dalam menyebarkan ajaran Kristen. Melalui pendekatan teologis, penelitian ini mencoba menjawab pertanyaan-pertanyaan mendasar tentang bagaimana misi Rasul Petrus memengaruhi perkembangan awal gereja dan bagaimana pengalaman pribadinya berinteraksi dengan panggilan ilahi. Ada pun metode yang penulis gunakan adalah Studi Pustaka Kajian ini juga mengeksplorasi dampak misi Rasul Petrus terhadap pemahaman teologis Kristen dan bagaimana kontribusinya membentuk landasan iman dalam tradisi Kristen. Dengan memahami peristiwa-peristiwa penting dalam sejarah misi Rasul Petrus, penelitian ini bertujuan untuk memberikan pemahaman yang lebih mendalam tentang peran teologisnya dalam konteks misi dan menyajikan pandangan yang komprehensif terkait pengaruhnya terhadap perkembangan ajaran Kristen. Implikasi teologis dari misi Rasul Petrus juga diperinci, menyoroti relevansinya dalam konteks kekristenan kontemporer.